Preparation of Medical Composites for X-ray Shielding - Belano, Lidia Solaz (My University, 2015)
It is generally difficult to assess distribution and dispersion of filler in composite material with methods and instruments available in the conventional laboratory setup. In this work dispersion and distribution of cupric oxide (copper (II) oxide) in ethylene vinyl acetate (EVA) polymer was studied. (i) Methods for evaluating mixing was investigated. (ii) Subsequently, mixing parameters was investigated. (iii) Finally, methods for increasing filler dispersion and distribution were investigated. It was found that light microscope could be used to analyse low filler loaded composites and dispersion index determined using a method outlined by T. Glaskova et al. It was also found that capillary rheometer could be used to analyse high filler loaded composites dispersion rheology and determine K and n values in the power law for non-newtonian liquids. A strong correlation was seen between the image analysis and the rheology analysis results. Improved mixing was achieved after 10 minutes of low speed mixing at a medium temperature. The comparing melt mixing with a Brabender melt mixer and an extruder, showed that extrusion gave better mixing results. Particle coalescence had minor significance during the latter material-processing step. Larger particle size distributions gave better mixing results (distribution and dispersion). The dispersion and distribution of CuO in EVA polymer strongly depended on the dispersability of the as-received CuO material. The surface properties of CuO were improved by adding suitable surface modifier (stearic acid). The obtained results, from the optical images, rheology measurements and from the tensile test show that the particle coating or powder stabilisation resulted in a better dispersion and distribution and composite materials with better mechanical properties.
Keywords: Materialvetenskap; Materialteknik; Materials Science; Materials Engineering